A gas diffusion electrode with a hydrophilic microporous layer and its preparation method and application
By introducing an ordered microporous silica microporous layer into the gas diffusion electrode, the problem of insufficient electrode water management capabilities is solved, the oxygen reduction performance and gas transmission efficiency are improved, and a longer and more efficient hydrogen peroxide production is achieved.
Patent Information
- Application Number
- CN202110258328.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-03-10
AI Technical Summary
When existing gas diffusion electrodes produce hydrogen peroxide due to oxygen reduction, the water management capacity is insufficient, resulting in increased electrochemical impedance and reduced oxygen reduction performance, making it difficult to apply on a large scale for a long time.
The microporous layer of ordered microporous silica is introduced between the support layer of the gas diffusion electrode and the catalyst layer. Through its hydrophilicity and ordered pore structure, the hydration and gas transmission efficiency of the electrode are improved, and the catalyst layer is prevented from flooding.
It achieves improved gas transmission efficiency and oxygen reduction yield while low electrochemical impedance, extends the service life of the electrode and reduces operating and maintenance costs.
Smart Images

Figure CN115084540B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a gas diffusion electrode with a hydrophilic microporous layer and a preparation method thereof, and application of the gas diffusion electrode as a cathode in electrochemical oxygen reduction to produce hydrogen peroxide. Background Art
[0002] Gas diffusion electrode is a thin membrane electrode stacked with multiple layers. It is widely used in fuel cells, metal-air batteries, electrocatalytic reduction, water treatment and other fields. Because it has a three-phase interface of gas, liquid and solid, it can promote the occurrence of cathode oxygen reduction. The gas diffusion electrode mainly consists of three parts: gas diffusion layer, support layer and catalyst layer. The waterproof and breathable gas diffusion layer provides an efficient transmission channel for the oxygen required for the reaction and has good water management performance; the support layer serves as the supporting skeleton of the gas diffusion electrode, which improves the mechanical strength of the electrode; the catalyst layer is close to the liquid phase side and is the place where the three-phase reaction occurs, providing a catalytic site for oxygen reduction.
[0003] At present, the efficiency of gas diffusion electrodes in producing hydrogen peroxide by oxygen reduction combined with electrochemical technology is limited by factors such as catalyst performance, electrode life, mechanical strength, and electrode water management performance, making it difficult to apply for a long time and on a large scale. Among them, water management is the most critical. Low hydration of the catalyst layer will lead to reduced proton conductivity and increased electrochemical impedance, which ultimately leads to reduced performance of oxygen reduction to produce hydrogen peroxide. In order to maintain sufficient hydration of the electrode, the gas is usually humidified before it is passed into the membrane electrolyzer. However, additional humidification devices further increase energy consumption and increase the cost of operating and maintenance systems.
[0004] At present, research on improving the performance of hydrogen peroxide production mainly focuses on two aspects: 1) the development of highly selective catalysts; 2) improving the utilization rate of oxygen. Summary of the invention
[0005] In view of the defects in the hydration capacity of previous gas diffusion electrodes, the purpose of the present invention is to provide a gas diffusion electrode that can improve the gas transmission efficiency and prevent the catalyst layer from being flooded while maintaining a low electrochemical impedance of the electrode. The gas diffusion electrode can be used as a cathode in electrochemical oxygen reduction to produce hydrogen peroxide, thereby improving the performance of the electrode in oxygen reduction to produce hydrogen peroxide.
[0006] In a first aspect, the present invention provides a gas diffusion electrode comprising: a gas diffusion layer located on one side of a support layer and a catalyst layer located on the other side of the support layer, a silica microporous layer being provided between the catalyst layer and the support layer, and a method for preparing the silica microporous layer comprising: mixing silica powder with a solvent and a binder and coating the mixed slurry on the other side of the support layer, followed by curing, wherein the silica is ordered microporous silica.
[0007] According to the present invention, a silicon dioxide microporous layer using ordered microporous silicon dioxide having an ordered microporous structure is introduced into a gas diffusion electrode, which can improve the hydration of the membrane electrode, enhance the proton transfer performance and the gas and liquid transmission efficiency, and thus improve the hydrogen peroxide yield. By introducing a silicon dioxide microporous layer using ordered microporous silicon dioxide, the hydration of the membrane electrode can be improved, the contact resistance between the catalyst layer and the substrate layer can be reduced, and gas and water can be redistributed, which has great application prospects.
[0008] When the mixed slurry is coated on the other side of the support layer, the loading amount of silica can be 0.3-3 mg / cm 2 The silicon dioxide used in the microporous layer may have a particle size of 100 to 500 nm, a pore size of 1 to 3 nm, and a specific surface area of 400 to 600 m 2 / g.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned gas diffusion electrode, comprising the following steps:
[0010] (1) Preparation of a gas diffusion layer: mixing graphite powder with a first solvent and a first binder, volatilizing the first solvent, and preparing a graphite / first binder paste; coating the graphite / first binder paste on one side of a support layer, and performing hot pressing and calcining;
[0011] (2) Preparation of a silica microporous layer: After mixing ordered microporous silica powder with a second solvent and a second binder to form a mixed slurry, the mixed slurry is coated on the other side of the support layer and cured to form a silica microporous layer;
[0012] (3) Preparation of the catalyst layer: mixing carbon black with a third solvent and a third binder, allowing the third solvent to volatilize, to prepare a carbon black / third binder paste; applying the carbon black / third binder paste to the surface of the silica microporous layer obtained in step (2), and performing hot pressing and calcining.
[0013] The support layer may be a support layer that has been pretreated as follows: immersing the support layer material in NaOH solution, HCl solution and water in turn for ultrasonic cleaning and drying, soaking it in polytetrafluoroethylene emulsion for 2 to 10 minutes after drying, taking it out and calcining it, and then repeating the above steps until the support layer gains weight by 10 to 30%.
[0014] The support layer material can be stainless steel mesh, nickel foam, titanium foam, titanium mesh, carbon paper or carbon cloth.
[0015] In step (1), the mass ratio of graphite powder to the first binder can be (2-6):1, and the first binder can be polytetrafluoroethylene emulsion.
[0016] In step (3), the mass ratio of carbon black to the third binder may be (2-6):1, and the third binder may be polytetrafluoroethylene emulsion.
[0017] In a third aspect, the present invention provides an application of the above-mentioned gas diffusion electrode in electrochemical oxygen reduction to produce hydrogen peroxide, which can be used in a gas electrochemical reduction electrolytic cell. For example, a gas electrochemical reduction electrolytic cell comprises the gas diffusion electrode according to any one of claims 1 to 3.
[0018] The present invention aims to improve the oxygen utilization rate to enhance the hydrogen peroxide production performance of the gas diffusion electrode. According to literature reports, the gas transmission rate of the gas diffusion electrode is affected by the hydrophilicity and pore structure of the diffusion layer, but the pores of the diffusion layer and the support layer of the gas diffusion electrode are all formed by the microporous structure of the material itself and the accumulation pores formed after the binder is sintered, and the amorphous pore structure is formed. In the traditional GDE (three-layer structure of diffusion layer, support layer, and catalyst layer), the gas directly diffuses to the catalyst layer through the diffusion layer and the support layer, and the formed airflow is turbulent, which is not conducive to the effective diffusion of the gas. It is not conducive to the efficient diffusion, contact, and reaction of oxygen at the catalytic site. Moreover, the catalyst layer and the support layer have high hydrophobicity and the hydrophobicity is higher than that of the catalyst layer. As the reaction proceeds, the water in the solution and the water produced by the side reaction of electrocatalytic oxygen reduction to produce hydrogen peroxide are easily accumulated in the gas diffusion pores to cause the occurrence of water flooding in the catalyst layer, hindering the diffusion of gas to the catalyst layer. In this regard, the gas diffusion electrode of the present invention adopts ordered microporous silica material. The ordered pore structure can rectify the gas entering through the diffusion layer, convert it into laminar flow, and make it diffuse evenly to the catalyst layer, thereby improving the diffusion and reaction efficiency of oxygen at the active site of the catalyst; at the same time, due to the different pore sizes and pore structures of the microporous layer and the support layer, the transmembrane liquid pressure difference will increase, and the hydrophilicity will be used to push water toward the liquid side. Prevent water from accumulating in the gas diffusion channel and reducing the gas transmission and diffusion efficiency. The gas diffusion electrode with a microporous silica layer prepared by the present invention can be used as a cathode to produce hydrogen peroxide by electrocatalytic oxygen reduction under neutral conditions, and can produce hydrogen peroxide efficiently and stably after long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A schematic diagram schematically shows the stacking order of the layers of a gas diffusion electrode according to an embodiment of the present invention;
[0020] Figure 2 A schematic diagram of the device of Example 7 is shown;
[0021] Figure 3 The test result diagram of Example 7 is shown;
[0022] Figure 4 The silica content of the microporous layer is 1 mg / cm 2Cyclic test data for testing the stability of the electrode in continuously producing hydrogen peroxide. DETAILED DESCRIPTION
[0023] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0024] The present disclosure relates to a gas diffusion electrode (such as an air diffusion electrode) used in, for example, a gas electrochemical reduction electrolytic cell. The preparation method of the gas diffusion electrode is simple and can efficiently reduce oxygen to produce a hydrogen peroxide solution with a certain concentration. The gas diffusion electrode comprises: a gas diffusion layer located on one side of a support layer and a catalyst layer located on the other side of the support layer, and a silica microporous layer is provided between the catalyst layer and the support layer. The preparation method of the silica microporous layer comprises: mixing ordered microporous silica powder with a solvent and a binder, applying the mixed slurry to the other side of the support layer, and then curing. For example, a gas diffusion electrode is formed by stacking and hot-pressing a gas diffusion layer, a support layer, a silica microporous layer (hydrophilic microporous layer) and a catalyst layer in sequence (see the stacking order). Figure 1 ), a hydrophilic microporous layer made of ordered microporous silica (ordered microporous silicon; MSL) is introduced between the gas diffusion layer (GDL) and the catalyst layer (CL) of the gas diffusion electrode. The introduction of the ordered hydrophilic microporous layer can improve the gas transmission efficiency while maintaining low electrochemical impedance of the electrode, which is conducive to efficient laminar diffusion of gas to the catalyst layer, improves the contact and reaction efficiency of gas and catalytic active sites, increases the contact area of the gas-liquid-solid three-phase interface, and thus promotes the occurrence of oxygen reduction to produce hydrogen peroxide reaction. The gas diffusion electrode disclosed in the present invention can be used as a cathode and applied to electrocatalytic oxygen reduction to synthesize hydrogen peroxide.
[0025] The preparation method of the gas diffusion electrode disclosed in the present invention may include optional pretreatment of the support layer, preparation of the gas diffusion layer, preparation of the hydrophilic microporous layer and preparation of the catalyst layer. The preparation method of the gas diffusion electrode disclosed in the present invention is exemplified below.
[0026] Support layer
[0027] The gas diffusion electrode disclosed in the present invention has a gas diffusion layer located on one side of the support layer and a catalyst layer located on the other side of the support layer, and a silicon dioxide microporous layer is provided between the catalyst layer and the support layer. The material of the support layer can use stainless steel mesh, nickel foam, titanium foam, titanium mesh, carbon paper or carbon cloth. The support layer is, for example, in the form of a plate, and the thickness can be 0.3-0.6 mm, for example, about 0.3 mm, and commercially available materials can be used, and the size can be adjusted as needed, for example, 5 cm×5 cm.
[0028] The support layer is a support layer that has been pretreated as follows: the support layer material is immersed in NaOH solution, HCl solution and water for ultrasonic cleaning and drying in turn, and then immersed in a binder such as polytetrafluoroethylene emulsion for 2 to 10 minutes after drying, and then calcined after being taken out, and then the above steps are repeated until the support layer gains weight by 10 to 30%. The concentration of the NaOH solution can be 2 to 5wt%, and the concentration of the HCl solution can be 2 to 5wt%. The mass concentration of the polytetrafluoroethylene emulsion used in the present disclosure can be 60%. The calcination temperature can be 250 to 400°C, and the time can be 25-75min. The hydrophobicity of the support layer can be enhanced by pretreatment, and the adhesion ability of the microporous layer / diffusion layer can be improved.
[0029] As an example, the pretreatment of the support layer includes: immersing the support layer material in 1M NaOH, 1M HCl and deionized water for ultrasonic cleaning for 30 to 60 minutes, and drying for use; then soaking it in polytetrafluoroethylene emulsion for 2 to 10 minutes, taking it out and air-drying it at room temperature, and then calcining it at 250 to 400°C for 40 minutes, and repeating the above steps until the support layer gains weight by 10 to 30%.
[0030] Preparation of gas diffusion layer
[0031] The preparation of the gas diffusion layer may include: mixing graphite powder with a solvent and a binder such as polytetrafluoroethylene emulsion, for example, dispersing graphite powder in an ethanol or isopropanol solution and then adding polytetrafluoroethylene emulsion, and waiting for the solvent to evaporate until the mixture is in a viscous paste; coating the paste on one side (surface) of the support layer, and performing hot pressing and calcining. The hot pressing may be performed at a pressure of 4 to 10 MPa and a temperature of 60 to 100° C. for 5 to 15 minutes, and then calcined at 300 to 400° C. for 20 to 60 minutes. The mass ratio of graphite powder to polytetrafluoroethylene emulsion may be (1.5 to 6):1, within which the ratio has the most suitable hydrophobic properties, and the pore structure / pore size distribution generated by carbonization and expansion of polytetrafluoroethylene after calcination is most conducive to gas diffusion, preferably (2 to 6):1. There is no particular limitation on the ethanol or isopropanol solution. For example, ethanol / isopropanol and other solvents can be added in excess during the slurry preparation, mixed evenly, and evaporated until the graphite powder forms a viscous paste (the catalyst layer preparation described later can be the same as this layer). The gas diffusion layer can be pressed to a thickness of 0.1-0.6 mm. The particle size of the graphite powder used can be 200 mesh.
[0032] As an example, the preparation of the gas diffusion layer includes: dispersing graphite powder in an ethanol or isopropanol solution, ultrasonically oscillating for 5 to 35 minutes, then adding a polytetrafluoroethylene emulsion, and continuing ultrasonication for 5 to 35 minutes, until the ethanol or isopropanol solution evaporates until the mixture becomes a viscous paste; the graphite / polytetrafluoroethylene paste is evenly applied to one side of the support layer, followed by hot pressing at a pressure of 4 to 10 MPa and a temperature of 60 to 100°C for 5 to 15 minutes, and then calcining at 300 to 400°C for 20 to 60 minutes.
[0033] Preparation of hydrophilic microporous layer
[0034] The preparation of the hydrophilic microporous layer may include: mixing ordered microporous silica powder (hereinafter, sometimes referred to as "silica powder") with a solvent and a binder, such as isopropanol / ethanol and a 5wt% Nafion solution to form a mixed slurry, coating it on the other side (surface) of the support layer, and curing it to form a silica microporous layer. In the present disclosure, the silica powder has a microporous channel structure, the silica particle size can be 100 to 500 nm, the pore size can be 1 to 3 nm (for example, including a pore size of about 2 nm), and the specific surface area can be 400 to 600 m 2 / g. Here, "ordered" refers to the pore size and pore structure distribution of porous materials, indicating that the pore size distribution is narrow and has a regular pore structure. The particle size of silica nanoparticles is not particularly limited, for example, it can be about 50nm. Every 10mg of silica can be mixed with 0.5-2.5ml (for example, 1ml) of solvent (or solvent and binder), for example ethanol / isopropanol: 5wt% Nafion = 0.8~0.95ml: 0.05~0.2ml, the total volume of ethanol / isopropanol and Nafion is 1ml. In some embodiments, anhydrous ethanol / isopropanol. The loading amount of silica on the surface on the other side of the support layer can be 0.3~3mg / cm 2 In one embodiment, the loading amount is 1 mg / cm 2 In this range, the efficiency of electrocatalytic production of hydrogen peroxide is the highest, the power consumption per kilogram of hydrogen peroxide is the lowest, and the hydrogen peroxide yield is the highest. The curing temperature can be 80-140°C, and the curing time can be 2 hours, which can be appropriately changed according to the load.
[0035] As an example, the preparation of the hydrophilic microporous layer includes: mixing silica powder with isopropanol and 5wt% Nafion solution, ultrasonicating for 30 minutes to make it evenly dispersed, and then spraying the mixed slurry evenly on the other side of the gas diffusion electrode prepared above, and then curing it at 80-140°C for 2h. The silica particles can be tetraethyl orthosilicate, which is slowly hydrolyzed in an ethanol solution of ammonia water at 0-25°C or in an ice bath to form silica gel, and then aged at low temperature to form silica powder. It can include: using tetraethyl orthosilicate (TEOS) as a silicon source, hexadecyltrimethylammonium bromide (CTAB) as a template, and ammonium fluoride as a catalyst, and synthesizing by a sol-gel method. The molar ratio of each substance during synthesis can be CTAB: TEOS: H2O: EtOH: NH4F = (0.2-2): 10: 80: 160: 1×10 -2 , respectively prepare ethanol aqueous solutions of CTAB and ammonium fluoride. Subsequently, TEOS is added dropwise to the mixed solution at 0-25°C, and stirred continuously until the mixture is uniformly mixed. Subsequently, it is transferred to room temperature, for example, stirred for 45 minutes to form a white gel. Aging is performed at 30-60°C, and then dried at 60-100°C for 24 hours. The sample is placed in a muffle furnace and calcined at 400-600°C for 2-6 hours. By adjusting the proportion of the template agent and the temperature in the reaction system, TEOS can be slowly hydrolyzed under mild conditions to form an ordered microporous structure. The pore structure and pore size of silica can be adjusted by adjusting the proportion of the template agent, the temperature of the reaction system, etc. during the synthesis process to achieve uniform pore size distribution of the microporous layer. The gas entering the GDE through the diffusion layer is rectified so that it diffuses evenly to the catalyst layer, so that oxygen forms an efficient gas-liquid-solid three-phase reaction interface in the catalyst layer to improve the reaction efficiency.
[0036] Preparation of catalyst layer
[0037] The preparation of the catalyst layer may include: mixing carbon black with a solvent and a binder such as polytetrafluoroethylene emulsion, for example, dispersing carbon black in an ethanol or isopropanol solution and then adding polytetrafluoroethylene emulsion, allowing the solvent to evaporate until the mixture is a viscous paste; applying the obtained carbon black / polytetrafluoroethylene paste to the surface of the silica microporous layer obtained above, and hot pressing and calcining. It can be hot pressed at a pressure of 4 to 10 MPa and a temperature of 60 to 100° C. for 5 to 15 minutes, and then calcined at 300 to 400° C. for 20 to 60 minutes. The mass ratio of carbon black to polytetrafluoroethylene emulsion can be (1.5 to 6): 1, and the catalyst layer has an optimal gas-liquid-solid three-phase reaction interface at this ratio, preferably (2 to 6): 1. After coating, it can be pressed into a catalyst layer with a thickness of 0.1-0.6 mm, and the thickness can be achieved by adjusting the roller press.
[0038] As an example, the preparation of the catalyst layer includes: dispersing carbon black into an ethanol or isopropanol solution, ultrasonically oscillating for 5 to 35 minutes, then adding polytetrafluoroethylene emulsion, continuing ultrasonication for 5 to 35 minutes, and waiting for the ethanol or isopropanol solution to evaporate until the mixture is a viscous paste; the carbon black / polytetrafluoroethylene paste is evenly applied to the surface of the hydrophilic microporous layer of the gas diffusion electrode obtained above, and then hot pressing at a pressure of 4 to 10 MPa and a temperature of 60 to 100°C for 5 to 15 minutes, and then calcining at 300 to 400°C for 20 to 60 minutes. Thus, a diffusion electrode with a hydrophilic microporous layer is obtained.
[0039] The gas diffusion electrode prepared by the above process can be used as a cathode in the electrochemical oxygen reduction synthesis of hydrogen peroxide under neutral conditions.
[0040] The present disclosure introduces a silica microporous layer based on hydrophilic ordered microporous silica between the support layer and the catalyst layer, which plays a role in redistributing gas and water, which is beneficial to improving the hydrophilicity of the electrode catalyst layer. At the same time, the ordered pore distribution of the microporous layer is beneficial to the efficient laminar diffusion of gas to the catalyst layer, improving the contact and reaction efficiency of gas and catalytic active sites, and can enhance the hydration of the electrode under low humidity (usually, an air pump is used to provide the oxygen required for oxygen reduction for the device, and there is a certain amount of water vapor in the air), thereby improving the proton transfer efficiency and the electrode conductivity. At the same time, the microporous silica layer can increase the transmembrane pressure difference, thereby adjusting the permeability of gas and liquid while maintaining the electrode hydration, further improving the electrode water management ability, and preventing the catalyst layer from being flooded. In addition, the stability of the electrode is enhanced, the contact area of the gas, liquid, and solid three-phase reaction interface is increased, and the oxygen reduction efficiency is improved. It is speculated that the reasons for the increase in the transmembrane liquid pressure difference include that the microporous layer has a pore size smaller than the support layer. The gas diffusion electrode with a silica microporous layer prepared by the present invention is used as a cathode, which can produce hydrogen peroxide by electrocatalytic oxygen reduction under neutral conditions, and can produce hydrogen peroxide efficiently and stably after long-term operation. According to the present invention, the presence of an ordered silica microporous layer can increase the transmembrane pressure difference, thereby adjusting the permeability of gas and liquid while maintaining electrode hydration, and preventing the catalyst layer from being flooded; usually, humidified air / oxygen is introduced to improve the diffusion / binding efficiency of oxygen at the electrolyte / catalyst (solid / liquid) interface to improve the oxygen reduction efficiency, and the hydrophilicity of the silica layer can be used to improve the distribution efficiency of oxygen at the electrolyte / catalyst (solid / liquid) interface, thereby achieving improved redox efficiency. In addition, the microporous layer is located between the support layer (such as carbon paper / carbon cloth / stainless steel mesh substrate) and the catalyst layer, and the microporous layer is conducive to adjusting the permeability of gas and liquid, and preventing the catalyst layer from being flooded. In addition, the content of PTFE and the calcination temperature affect the hydrophilicity and pore structure distribution of the GDE diffusion layer, thereby affecting the gas diffusion performance of the GDE; similarly, the binder content and calcination temperature in the preparation conditions affect the hydrophilicity and hydrophobicity of the catalyst layer (affecting the interface reaction efficiency) and thus affecting the oxygen reduction efficiency of the catalyst. The present disclosure is directed to the field of electrocatalytic hydrogen peroxide production, and the functions of the microporous layer include: the microporous silica used has an ordered pore structure and a uniform pore size, which is conducive to the uniform diffusion of gas to the catalyst layer, thereby improving the efficiency of electrocatalytic oxygen reduction to produce hydrogen peroxide; using its hydrophilicity, water vapor and water generated by the reaction are transmitted to the liquid phase side to prevent gas channel blockage.
[0041] Beneficial effects of the present invention:
[0042] The gas diffusion electrode disclosed in the present invention adds a hydrophilic microporous silica material between the support layer and the catalyst layer, which is beneficial to improving the hydrophilicity of the catalyst layer while maintaining low electrochemical impedance of the electrode. At the same time, the orderly pore distribution of the microporous layer is beneficial to the efficient laminar diffusion of gas to the catalyst layer, improving the contact and reaction efficiency between the gas and the catalytic active sites, so that the electrode maintains good hydration under low air flow humidity, and improves the proton transfer efficiency and electrode conductivity. At the same time, the microporous silica layer can increase the transmembrane pressure difference, thereby adjusting the permeability of gas and liquid while maintaining electrode hydration, further improving the electrode water management ability, and preventing the catalyst layer from being flooded;
[0043] The present invention focuses on regulating the hydration of membrane electrodes, introduces a hydrophilic microporous silica layer into a traditional gas diffusion electrode, optimizes the gas and liquid transmission efficiency of the electrode, improves the hydration of the electrode, and is more conducive to the transmission of oxygen and the transfer of protons, thereby improving the performance of the electrode in producing hydrogen peroxide by oxygen reduction.
[0044] The following further exemplifies the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only an example within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description of this article, and are not limited to the specific values exemplified below;
[0045] In the following examples, the reagents, materials and instruments used are conventional reagents, conventional materials and conventional instruments unless otherwise specified, and are all commercially available. The reagents involved can also be synthesized by conventional synthesis methods.
[0046] Embodiment 1:
[0047] Preparation of silica particles:
[0048] Tetraethyl orthosilicate (TEOS) was used as the silicon source, CTAB) was used as the template, and ammonium fluoride was used as the catalyst. The molar ratio of each substance during the synthesis was CTAB: TEOS: H2O: EtOH: NH4F = 1: 10: 80: 160: 1×10 -2 , add ammonium fluoride to the ethanol aqueous solution and stir until dissolved. Then, add TEOS dropwise to the mixed solution at 0°C while stirring, and continue stirring until the mixture is uniform. Then, transfer to room temperature and stir for 45 minutes until a white gel is formed. Aging at 40°C, followed by drying at 80°C for 24 hours. The sample is placed in a muffle furnace and calcined at 550°C for 4 hours;
[0049] Preparation of gas diffusion electrode:
[0050] (1) Pretreatment of the support layer: The support layer material was immersed in 1M NaOH, 1M HCl and deionized water for ultrasonic cleaning for 60 min, and then dried for use. Then, it was immersed in polytetrafluoroethylene emulsion for 3 min, taken out and air-dried at room temperature, and then calcined at 250°C for 40 min. The above steps were repeated until the support layer gained 10% in weight;
[0051] (2) Preparation of gas diffusion layer: 3 g of graphite powder was dispersed in an ethanol solution and ultrasonically vibrated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of 3:2. The ultrasonication was continued for 30 min. The ethanol solution was evaporated until the mixture became a viscous paste. The graphite / polytetrafluoroethylene paste was evenly applied to one side of the support layer with a coating thickness of 0.3 mm. Then, it was hot-pressed at a pressure of 4 MPa and a temperature of 60°C for 15 min, and then calcined at 300°C for 40 min.
[0052] (3) Preparation of hydrophilic microporous layer: SiO2 powder was mixed with 1.5 ml isopropanol and 10 uL 5 wt% Nafion solution, and then ultrasonicated for 30 minutes to make it uniformly dispersed. Then, the mixed slurry was evenly sprayed onto the other side of the gas diffusion electrode prepared in step (2) to make the silica loading reach 1 mg / cm 2 , then cured at 140°C for 2h;
[0053] (4) Preparation of catalyst layer: 3 g of carbon black was dispersed in an ethanol solution and ultrasonically oscillated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of carbon black to polytetrafluoroethylene emulsion of 3:2 for more than 30 min. The ethanol solution was evaporated until the mixture was a viscous paste. The carbon black / polytetrafluoroethylene paste was evenly applied to the surface of the hydrophilic microporous layer of the gas diffusion electrode obtained in step (3) to a coating thickness of 0.1 mm. Then, the mixture was hot-pressed at a pressure of 4 MPa and a temperature of 60°C for 15 min, and then calcined at 300°C for 40 min to obtain a gas diffusion electrode with a hydrophilic microporous layer.
[0054] Embodiment 2:
[0055] (1) Pretreatment of the support layer: The support layer material was immersed in 1M NaOH, 1M HCl and deionized water for ultrasonic cleaning for 60 min, and then dried for use. Then, it was immersed in polytetrafluoroethylene emulsion for 3 min, taken out and air-dried at room temperature, and then calcined at 350°C for 40 min. The above steps were repeated until the support layer gained 30% in weight;
[0056] (2) Preparation of gas diffusion layer: 3 g of graphite powder was dispersed in an ethanol solution and ultrasonically vibrated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of 3:1 between graphite powder and polytetrafluoroethylene emulsion. The ultrasonication was continued for 30 min until the ethanol solution evaporated until the mixture became a viscous paste. The graphite / polytetrafluoroethylene paste was evenly applied to one side of the support layer with a coating thickness of 0.3 mm. Then, the mixture was hot-pressed at a pressure of 8 MPa and a temperature of 80°C for 15 min, and then calcined at 350°C for 60 min.
[0057] (3) Preparation of hydrophilic microporous layer: Silica powder was mixed with 1.5 ml isopropanol and 10 uL 5 wt% Nafion solution, and then ultrasonicated for 30 minutes to make it uniformly dispersed. Then, the mixed slurry was evenly sprayed onto the other side of the gas diffusion electrode prepared in step (2) to make the silica loading reach 0.7 mg / cm 2 , then cured at 120°C for 2h;
[0058] (4) Preparation of catalyst layer: 3 g of carbon black was dispersed in an ethanol solution and ultrasonically oscillated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of carbon black to polytetrafluoroethylene emulsion of 3:1 for more than 30 min. The ethanol solution was evaporated until the mixture was a viscous paste. The carbon black / polytetrafluoroethylene paste was evenly applied to the surface of the hydrophilic microporous layer of the gas diffusion electrode obtained in step (3) to a coating thickness of 0.1 mm. Then, the mixture was hot-pressed at a pressure of 8 MPa and a temperature of 80°C for 15 min, and then calcined at 350°C for 60 min to obtain a gas diffusion electrode with a hydrophilic microporous layer.
[0059] Embodiment 3:
[0060] (1) Pretreatment of the support layer: The support layer material was immersed in 1M NaOH, 1M HCl and deionized water for ultrasonic cleaning for 60 min, and then dried for use. Then, it was immersed in polytetrafluoroethylene emulsion for 3 min, taken out and air-dried at room temperature, and then calcined at 300°C for 40 min. The above steps were repeated until the support layer gained 20% in weight;
[0061] (2) Preparation of gas diffusion layer: 3 g of graphite powder was dispersed in an isopropanol solution and ultrasonically vibrated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of 6:1 of graphite powder to polytetrafluoroethylene emulsion, and ultrasonication was continued for 30 min. The ethanol solution was evaporated until the mixture became a viscous paste. The graphite / polytetrafluoroethylene paste was evenly applied to one side of the support layer with a coating thickness of 0.3 mm. Then, it was hot-pressed at a pressure of 6 MPa and a temperature of 100°C for 5 min, and then calcined at 400°C for 20 min.
[0062] (3) Preparation of hydrophilic microporous layer: Silica powder was mixed with 1.5 ml of isopropanol and 10 uL of 5 wt% Nafion solution, and then the mixed slurry was evenly sprayed onto the other side of the gas diffusion electrode prepared in step (2) to achieve a silica loading of 0.3 mg / cm 2 , then cured at 80°C for 2h;
[0063] (4) Preparation of catalyst layer: 3 g of carbon black was dispersed in an isopropanol solution and ultrasonically oscillated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of carbon black to polytetrafluoroethylene emulsion of 6:1 for more than 30 min. The ethanol solution was evaporated until the mixture was in a viscous paste. The carbon black / polytetrafluoroethylene paste was evenly applied to the surface of the hydrophilic microporous layer of the gas diffusion electrode obtained in step (3) to a coating thickness of 0.1 mm. Then, the mixture was hot-pressed at a pressure of 6 MPa and a temperature of 100° C. for 5 min, and then calcined at 400° C. for 20 min to obtain a gas diffusion electrode with a hydrophilic microporous layer.
[0064] Embodiment 4:
[0065] (1) Pretreatment of the support layer: The support layer material was immersed in 1M NaOH, 1M HCl and deionized water for ultrasonic cleaning for 60 minutes, and then dried for use. Then, it was immersed in polytetrafluoroethylene emulsion for 3 minutes, taken out and air-dried at room temperature, and then calcined at 400°C for 40 minutes. The above steps were repeated until the support layer gained 10% in weight;
[0066] (2) Preparation of gas diffusion layer: 3 g of graphite powder was dispersed in an ethanol solution and ultrasonically vibrated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of 3:2 of graphite powder to polytetrafluoroethylene emulsion, and ultrasonication was continued for 30 min. The ethanol solution was evaporated until the mixture became a viscous paste. The graphite / polytetrafluoroethylene paste was evenly applied to one side of the support layer with a coating thickness of 0.3 mm. Then, it was hot-pressed at a pressure of 10 MPa and a temperature of 90°C for 10 min, and then calcined at 400°C for 50 min.
[0067] (3) Preparation of hydrophilic microporous layer: Silica powder was mixed with 1.5 ml of isopropanol and 10 uL of 5 wt% Nafion solution, and then ultrasonicated for 30 minutes to make it uniformly dispersed. Then, the mixed slurry was evenly sprayed onto the other side of the gas diffusion electrode prepared in step (2) to make the silica loading reach 0.5 mg / cm 2 , then cured at 100°C for 2h;
[0068] (4) Preparation of catalyst layer: 3 g of carbon black was dispersed in an ethanol solution and ultrasonically oscillated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of carbon black to polytetrafluoroethylene emulsion of 3:2 for more than 30 min. The ethanol solution was evaporated until the mixture was a viscous paste. The carbon black / polytetrafluoroethylene paste was evenly applied to the surface of the hydrophilic microporous layer of the gas diffusion electrode obtained in step (3) to a coating thickness of 0.1 mm. Then, the mixture was hot-pressed at a pressure of 10 MPa and a temperature of 90°C for 10 min, and then calcined at 400°C for 50 min to obtain a gas diffusion electrode with a hydrophilic microporous layer.
[0069] Embodiment 5:
[0070] (1) Pretreatment of the support layer: The support layer material was immersed in 1M NaOH, 1M HCl and deionized water for ultrasonic cleaning for 60 min, and then dried for use. Then, it was immersed in polytetrafluoroethylene emulsion for 3 min, taken out and air-dried at room temperature, and then calcined at 300°C for 40 min. The above steps were repeated until the support layer gained 20% in weight;
[0071] (2) Preparation of gas diffusion layer: 3 g of graphite powder was dispersed in an ethanol solution and ultrasonically vibrated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of 6:1 of graphite powder to polytetrafluoroethylene emulsion, and ultrasonication was continued for 30 min. The ethanol solution was evaporated until the mixture became a viscous paste. The graphite / polytetrafluoroethylene paste was evenly applied to one side of the support layer with a coating thickness of 0.3 mm. Then, it was hot-pressed at a pressure of 6 MPa and a temperature of 100°C for 5 min, and then calcined at 400°C for 20 min.
[0072] (3) Preparation of hydrophilic microporous layer: Silica powder was mixed with 1.5 ml of isopropanol and 10 uL of 5 wt% Nafion solution, and then the mixed slurry was evenly sprayed onto the other side of the gas diffusion electrode prepared in step (2) to achieve a silica loading of 0.3 mg / cm 2 , then cured at 100°C for 2h;
[0073] (4) Preparation of catalyst layer: 3 g of carbon black was dispersed in an ethanol solution and ultrasonically oscillated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of carbon black to polytetrafluoroethylene emulsion of 6:1 for more than 30 min. The ethanol solution was evaporated until the mixture was in a viscous paste. The carbon black / polytetrafluoroethylene paste was evenly applied to the surface of the hydrophilic microporous layer of the gas diffusion electrode obtained in step (3) to a coating thickness of 0.1 mm. Then, the mixture was hot-pressed at a pressure of 6 MPa and a temperature of 100° C. for 5 min, and then calcined at 400° C. for 30 min to obtain a gas diffusion electrode with a hydrophilic microporous layer.
[0074] Embodiment 6:
[0075] (1) Pretreatment of the support layer: The support layer material was immersed in 1M NaOH, 1M HCl and deionized water for ultrasonic cleaning for 60 min, and then dried for use. Then, it was immersed in polytetrafluoroethylene emulsion for 3 min, taken out and air-dried at room temperature, and then calcined at 350°C for 40 min. The above steps were repeated until the support layer gained 30% in weight;
[0076] (2) Preparation of gas diffusion layer: 3 g of graphite powder was dispersed in an isopropanol solution and ultrasonically vibrated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of 3:1 between graphite powder and polytetrafluoroethylene emulsion. The ultrasonication was continued for 30 min. The ethanol solution was evaporated until the mixture became a viscous paste. The graphite / polytetrafluoroethylene paste was evenly applied to one side of the support layer with a coating thickness of 0.3 mm. Then, the mixture was hot-pressed at a pressure of 8 MPa and a temperature of 100°C for 15 min, and then calcined at 350°C for 40 min.
[0077] (3) Preparation of hydrophilic microporous layer: Silica powder was mixed with 1.5 ml of isopropanol and 10 uL of 5 wt% Nafion solution, and then ultrasonicated for 30 minutes to make it uniformly dispersed. Then, the mixed slurry was evenly sprayed onto the other side of the gas diffusion electrode prepared in step (2) to make the silica loading reach 0.5 mg / cm 2 , then cured at 100°C for 2h;
[0078] (4) Preparation of catalyst layer: 3 g of carbon black was dispersed in an isopropanol solution and ultrasonically oscillated for 30 min. Then, polytetrafluoroethylene emulsion was added at a mass ratio of carbon black to polytetrafluoroethylene emulsion of 3:1 for more than 30 min. The ethanol solution was evaporated until the mixture became a viscous paste. The carbon black / polytetrafluoroethylene paste was evenly applied to the surface of the hydrophilic microporous layer of the gas diffusion electrode obtained in step (3) to a coating thickness of 0.1 mm. Then, the mixture was hot-pressed at a pressure of 8 MPa and a temperature of 100° C. for 15 min, and then calcined at 350° C. for 40 min to obtain a gas diffusion electrode having a hydrophilic microporous layer.
[0079] Example 7: Under neutral electrolyte conditions, an experiment of electrocatalytic oxygen reduction to produce hydrogen peroxide was carried out using the gas diffusion electrode prepared in the example as a cathode. The specific operation process is as follows:
[0080] The experiment was carried out using a three-chamber electrolytic cell. The anode and cathode chambers were separated by a proton exchange membrane (Nafion 117). The titanium mesh coated with ruthenium / iridium was used as the anode, and the gas diffusion electrode prepared in the embodiment was used as the cathode. The spacing between the two electrodes was 3 cm, and the effective working area was 16 cm. 2100mM sodium sulfate solution was used as the electrolyte, and the hydraulic retention time was 3min. A DC regulated power supply was used to control the current density to 30mA / cm 2 1L / min of air was introduced by an air pump. 1ml of sample was taken every 2-5min within 60min, and the concentration of hydrogen peroxide was determined by a spectrophotometer using the titanium salt complexation method.
[0081] The efficiency and stability of the long-term electrocatalytic oxygen reduction to produce hydrogen peroxide of the gas diffusion electrode prepared in the example were tested under neutral electrolyte conditions. The specific operation process is as follows:
[0082] The experiment was carried out using a three-chamber electrolytic cell. The anode and cathode chambers were separated by a proton exchange membrane (Nafion 117). The titanium mesh coated with ruthenium / iridium was used as the anode, and the gas diffusion electrode prepared in Examples 1 to 4 was used as the cathode. The spacing between the two electrodes was 3 cm, and the effective working area was 16 cm. 2 . 50mM sodium sulfate solution was used as the electrolyte, and the hydraulic retention time was 3min. A DC regulated power supply was used to control the current density to 3mA / cm 2 1L / min of air was introduced by an air pump. 1ml of sample was taken every 2-10h to determine the concentration of hydrogen peroxide and the hydrogen peroxide yield was monitored within 200h.
[0083] Table 1: At loadings of 0, 0.5, 1, and 3 mg / cm 2 The experiment was carried out under the conditions of (microporous layer);
[0084]
[0085] In the electrochemical hydrogen peroxide production experiment, the silica content of the microporous layer was 1 mg / cm 2 The stability of the electrode in continuously producing hydrogen peroxide was tested. The cycle test data is shown in the figure. Figure 4 .
Claims
1. A gas diffusion electrode, characterized in that: The invention comprises: a gas diffusion layer located on one side of a support layer and a catalyst layer located on the other side of the support layer, a silicon dioxide microporous layer is provided between the catalyst layer and the support layer, and a preparation method of the silicon dioxide microporous layer comprises: mixing silicon dioxide powder with a solvent and a binder, coating the mixed slurry on the other side of the support layer, and then curing, and the silicon dioxide is ordered microporous silicon dioxide.
2. The gas diffusion electrode according to claim 1, characterized in that When the mixed slurry is coated on the other side of the support layer, the loading amount of silica is 0.3-3 mg / cm 2 .
3. The gas diffusion electrode according to claim 1 or 2, characterized in that: The silica particles used in the microporous layer are 100-500nm in size, 1-3nm in pore size, and 400-600m in specific surface area. 2 / g.
4. A method for preparing a gas diffusion electrode according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Preparation of a gas diffusion layer: mixing graphite powder with a first solvent and a first binder, volatilizing the first solvent, and preparing a graphite / first binder paste; coating the graphite / first binder paste on one side of a support layer, and performing hot pressing and calcining; (2) Preparation of a silica microporous layer: After mixing ordered microporous silica powder with a second solvent and a second binder to form a mixed slurry, the mixed slurry is coated on the other side of the support layer and cured to form a silica microporous layer; (3) Preparation of the catalyst layer: mixing carbon black with a third solvent and a third binder, volatilizing the third solvent, and preparing a carbon black / third binder paste; applying the carbon black / third binder paste to the surface of the silica microporous layer obtained in step (2), and performing hot pressing and calcining.
5. The preparation method according to claim 4, characterized in that: The support layer is a support layer that has been pretreated as follows: the support layer material is immersed in NaOH solution, HCl solution and water in turn for ultrasonic cleaning and drying, and then immersed in polytetrafluoroethylene emulsion for 2 to 10 minutes after drying, and then taken out and calcined, and then the above steps are repeated until the support layer increases in weight by 10 to 30%.
6. The preparation method according to claim 5, characterized in that: The support layer material is stainless steel mesh, nickel foam, titanium foam, titanium mesh, carbon paper or carbon cloth.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (1), the mass ratio of graphite powder to the first binder is (2-6):
1.
8. The preparation method according to any one of claims 4 to 7, characterized in that In step (3), the mass ratio of carbon black to the third binder is (2-6):
1.
9. Use of the gas diffusion electrode according to any one of claims 1 to 3 in electrochemical oxygen reduction to produce hydrogen peroxide.
10. A gas electrochemical reduction electrolytic cell, characterized in that: A gas diffusion electrode according to any one of claims 1 to 3.
Citation Information
Patent Citations
Ordered gas diffusion electrode, and production method and application thereof
CN104716333A
Enhanced gas diffusion layer microporous membrane for fuel cell membrane electrode, membrane electrode and preparation method thereof
CN109950551A